Variation in brain's effective connectivity due to driving using partial directed coherence - Almahasneh, H. (2019)
In this paper, changes in brain's causal connectivity due to the driving process have been studied using Partial Directed Coherence (PDC) and compared with the state of open eyes. The EEG samples collected from 20 subjects using 128-channel EGI setup have been used. PDC has been calculated between 12 electrodes dispersed over the skull according to the 10-20 standard in theta, alpha and beta bands and analyzed. Results show interesting distribution of brain connections between the anterior and the posterior regions during driving. The variation in causal connectivity due to driving is compared with the EO state in the three bands of theta, alpha, and beta and reported. Â©2018 IEEE.